United States in Latin America : A quarter century of crisis and challenge, 1961-1986 - Martz, John D., ed (Lincoln : University of Nebraska Press, 1989)
Political and policy making, 1. -- The Kennedy - Johnson years, 3. -- The Carter administration and Latina America : A test of principle, 61. -- Not what I say, but what I do : Latin American policy in the Reagan administration, 98. -- Crisis management : Interventionism and negotiation, 133. -- The dominican intervention revisited : An attitudinal and operational analysis, 135. -- Crisis management : Chile and marxism, 157. -- Negotiating the 1978 Panama Canal treaties : contending theorical perspectives, 175. -- War in the South Atlantic, 202. -- Toward the Twenty-first century : Challenges and opportunities, 235. -- The United States, Central America, and the Caribbean, 260. -- Castro, Latin America, an the United States, 288. -- Images, intervention, and the cause of democracy, 307. -- The contributors, 331